Analysis of Health Protocol Application to Compliance Level In Informal Workers During the Covid-19 Pandemic - Maria Goretti Catur Yuantari; Enny Rachmani; Eti Rimawati; Sri Handayani; Edi Jaya Kusuma (Dian Nuswantoro Semarang, 2021)
Objective and Background: The high number of Covid-19 cases until the end of 2020 is acomplicated problem in all countries including Indonesia. The dilemma between health choices or thecontinuity of life to keep working and making ends meet has become a struggle during the Covid-19pandemic. The purpose of this study was to analyze the application of health protocols to the level ofadherence to informal workers during the Covid-19 pandemic.Method: This research method using cross-sectional, data collection was done by interviewmethod. The population of this research is in the informal work unit in the district Tanjung MasSemarang, and we obtained a sample of 52 respondents. Data processing SPSS program andbivariate test using Fisher Exact Test.Result: The results of this study are there is a relationship between the application of healthprotocols with the level of compliance in the workplace with a p-value of 0.000. The low availability ofsanitation facilities in implementing health protocols by workplace leaders and the lack of monitoringby leaders are one of the reasons for the high number of Covid-19 cases.Keywords: Covid-19, health protocol, level of compliance, workplace.